Long-Term Spinal Cord Stimulation After Chronic Complete Spinal Cord Injury Enables Volitional Movement in the Absence of Stimulation - Peña Pino, Isabela; Hoover, Caleb; Venkatesh, Shivani; Ahmadi, Aliya; Sturtevant, Dylan; Patrick, Nick; Freeman, David; Parr, Ann; Samadani, Uzma; Balser, David; Krassioukov, Andrei; Phillips, Aaron; et al. (Frontiers in Systems Neuroscience, 2020)
Background: Chronic spinal cord injury (SCI) portends a low probability of recovery, especially in the most severe subset of motor-complete injuries. Active spinal cord stimulation with or without intensive locomotor training has been reported to restore movement after traumatic SCI. Only three cases have been reported where participants developed restored volitional movement with active stimulation turned off after a period of chronic stimulation and only after intensive rehabilitation with locomotor training. It is unknown whether restoration of movement without stimulation is possible after stimulation alone. Objective: We describe the development of spontaneous volitional movement (SVM) without active stimulation in a subset of participants in the Epidural Stimulation After Neurologic Damage (ESTAND) trial, in which locomotor training is not prescribed as part of the study protocol, and subject’s rehabilitation therapies are not modified. Methods: Volitional movement was evaluated with the Brain Motor Control Assessment using sEMG recordings and visual examination at baseline and at follow-up visits with and without stimulation. Additional functional assessment with a motor-assisted bicycle exercise at follow-up with and without stimulation identified generated work with and without effort. Results: The first seven participants had ASIA Impairment Scale (AIS) A or B thoracic SCI, a mean age of 42 years, and 7.7 years post-injury on average. Four patients developed evidence of sustained volitional movement, even in the absence of active stimulation after undergoing chronic epidural spinal cord stimulation (eSCS). Significant increases in volitional power were found between those observed to spontaneously move without stimulation and those unable (p < 0.0005). The likelihood of recovery of spontaneous volitional control was correlated with spasticity scores prior to the start of eSCS therapy (p = 0.048). Volitional power progressively improved over time (p = 0.016). Additionally, cycling was possible without stimulation (p < 0.005). Conclusion: While some SVM after eSCS has been reported in the literature, this study demonstrates sustained restoration without active stimulation after long-term eSCS stimulation in chronic and complete SCI in a subset of participants. This finding supports previous studies suggesting that “complete” SCI is likely not as common as previously believed, if it exists at all in the absence of transection and that preserved pathways are substrates for eSCS-mediated recovery in clinically motor-complete SCI. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03026816.